The role of photodynamic therapy in overcoming cancer drug resistance. Issue 8 (29th August 2015) - Spring, Bryan Q.; Rizvi, Imran; Xu, Nan; Hasan, Tayyaba
<x xml:space="preserve">Abstract</x> This perspective highlights unique mechanisms of photodynamic therapy (PDT) that can be utilized to overcome classical drug resistance and re-sensitize resistant cancer cells for standard therapies.